2020
DOI: 10.1186/s12888-020-02490-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal resting-state functional connectivity of hippocampal subfields in patients with major depressive disorder

Abstract: Background: Many studies have found that the hippocampus plays a very important role in major depressive disorder (MDD). The hippocampus can be divided into three subfields: the cornu ammonis (CA), dentate gyrus (DG) and subiculum. Each subfield of the hippocampus has a unique function and are differentially associated with the pathological mechanisms of MDD. However, no research exists to describe the resting state functional connectivity of each hippocampal subfield in MDD. Methods: Fifty-five patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 77 publications
(73 reference statements)
2
19
0
1
Order By: Relevance
“…Molecular and cellular studies have examined the intracellular signaling pathways involved in the regulation of synaptic function by stress. Notably in the hippocampus, decreased neuroplasticity and synapse function in the dentate gyrus and CA sub-regions have been associated with causing depression-like behaviors (Law et al, 2016;Hao et al, 2020). Dendrites, for example, receive messages for the cell, allowing neurons to communicate with other neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and cellular studies have examined the intracellular signaling pathways involved in the regulation of synaptic function by stress. Notably in the hippocampus, decreased neuroplasticity and synapse function in the dentate gyrus and CA sub-regions have been associated with causing depression-like behaviors (Law et al, 2016;Hao et al, 2020). Dendrites, for example, receive messages for the cell, allowing neurons to communicate with other neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, investigating reward processing in MDD may offer additional insight into how dysregulated reward networks may also contribute to substance use. Participants with MDD exhibit attenuated functional connectivity between the VS and cortical regions, such as the vmPFC and OFC (Furman et al, 2011;Hao et al, 2020). A meta-analysis of fMRI research assessing reward processing in MDD revealed distinct abnormalities within reward circuitry, such as a hyporesponsive ventral striatum and hyperresponsive OFC (Ng et al, 2019).…”
Section: Reward Hyposensitivity Modelmentioning
confidence: 99%
“…Thus, investigating reward processing in MDD may offer additional insight into how dysregulated reward networks may also contribute to substance use. Participants with MDD exhibit attenuated functional connectivity between the VS and cortical regions, such as the vmPFC and OFC [ 33 , 34 ]. A meta-analysis of fMRI research assessing reward processing in MDD revealed distinct abnormalities within reward circuitry, such as a hyporesponsive ventral striatum and hyperresponsive OFC [ 35 ].…”
Section: Significancementioning
confidence: 99%